Progress and Perspectives of Single‐Atom Catalysts for Gas Sensing. Issue 3 (29th November 2022) - Chu, Tianshu; Rong, Chao; Zhou, Lei; Mao, Xinyuan; Zhang, Bowei; Xuan, Fuzhen
Abstract: Single‐atom catalysts (SACs) attract extensive attention in the field of heterogeneous catalysis in recent years due to the maximum atom utilization and unique physical and chemical properties. The gas sensing is actually a heterogeneous catalysis process but the SACs are new to this area. Although SACs show huge potential in gas sensing, the SACs gas sensing area currently is still at the infancy stage. This work critically reviews the recent advances and current status of single‐atom gas sensing materials. General synthesis routes, characterization methods, and sensing performance indexes are introduced. At the end, the challenges and future prospects on SACs gas sensing are presented from the authors' perspectives. This work is anticipated to provide insights and guideline for the chemical sensing community. Abstract : Gas sensors are widely used in many areas. Compared to the traditional sensing materials including semiconductors, nanomaterials, and 2D materials, the emerging single‐atom catalysts (SACs) show great potential owing to the maximum atom utilization and unique chemical and physical properties. This work timely summarizes the recent progress and provides future perspectives on the SACs sensing.